Hybrid identities: gender identity construction in the contemporary Moroccan diaspora novels - Aouaki, Soukaina (Université sidi mohamed ben abdellah, Faculté des lettres et des sciences humaines-Sais-Fès, 2019)
This thesis tries to analyze the contemporary Moroccan diasporic novel to decipher how the diasporic subjects express their exile experience and how their gender and cultural identities are shaped in a hybrid context. In fact, the question of cultural and political relations between Morocco and Europe has always been a subject matter. Identity crisis has been a vital component in the migrant’s literary works. This work wants to look at the following concepts home, hybridity, gender and identity construction by using a number of theories while analyzing the literary works of some Moroccan diaspora writers. Therefore, it tries to demonstrate, that the dream of trespass of many Moroccans which might seems appealing at the beginning but turns out a burden once diaspora subjects are faced with cultural shock, problems of integration, or just when the feeling of yearning for home dominates their souls. It is here where the myth of return starts haunting them and creating another problem when home, the problem of belonging. Therefore, the utopian dream of the west becomes contradictory and creates huge ambivalence. This dissertation is divided into two major parts. A theoretical part that offers an overview over the major postcolonial and gender theories beside shedding light on the main concepts such as home, exile, displacement, gender and cultural identity. The second part deals with Moroccan diasporic novels from canonized as well as uncannonized writers with particular emphasis on Leaving Tangier, The Last Patriarch, French Dream, Zeida de Nulle Part, and Une Femme tout Simplement where they represent a study of the development of the author’s exile experience through their characters.
Keywords: Diaspora; Identity; Home; Third-space; Gender; Migration and cultural conflict; Hybridity.